LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM SOLVING POLYA - Nurliawaty, Lilis; Mujasam, M; Yusuf, Irfan; Widyaningsih, Sri Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Lack of exact use of teaching materials and does not correspond to the needs of student leads to lack of analytical ability of students to the process of problem solving. Research development worksheets based on Polya problem solving on the heat material aims to develop valid LKPD, practical, and effective. Stages of development using the 4D model was modified into 3D, namely define (definition), Design (planning), and Development (development) The results of the validity of the learning device in the category valid, obtained from the calculation of CVI are in the range 0-1 and said in category reliably with r11 value greater than rtabel (rcount > rtabel). The results of the analysis of questionnaire responses of students obtained an average percentage of 87.9% on the analysis. The analysis result of sheets assessment of learning physics used LKPD-based Polya problem solving obtained average percentage analysis results in the first meeting is 77.33% with good category, the average percentage of the results of the analysis at the second meeting is 81.11% with a very good category and average of results percentage analysis at the third meeting is 78.89% with good category. So it can say that LKPD-based Polya problem solving developed valid, practical and effective to use.